(untitled) (Journal of Partial Differential Equations, 2002)
Local W^1,q estimates for weak solutions to a class of equations in divergence form D_i(a_ij(x)|Du|^p-2D_ju) = 0 are obtained, where q > p is given. These estimates are very important in obtaining higher regularity for the weak solutions to elliptic equations.